Medical Multimedia Retrieval 2.0 - Müller, H. (Yearbook of Medical Informatics, 2008)
Objectives The objective of this article is to provide an overview of current trends in medical multimedia retrieval. This state of the art is then compared with trends and techniques in the Web 2.0 field that addresses several of the problems of current multimedia retrieval and may help in solving them.MethodsThe article uses a review of the current literature on medical imaging and medical multimedia retrieval from the Pubmed and Google scholar literature search engines. Other sources include popular Web 2.0 web pages and articles on Web 2.0 describing the main concepts of these technologies in the medical domain.Results Web 2.0 has significantly changed the way we interact with the Internet and has created an important added-value by promoting activities of users and interactions between users. In the medical field, there are many examples of adoption of these methods and multimedia retrieval can play an important role in this field by supplying the right data at the right time.Conclusions Medical multimedia retrieval still has a long way to go to become an everyday tool in the medical field and in clinical practice. Still, when reusing and linking much of the electronic patient record’s data, image retrieval can be a technology to help extract important knowledge and navigate through the large amounts of data. Key challenges for more widespread adoption of these technologies involve legal rules for secondary use of medical data because currently only very few image data sets with ground truth have been made available.
Keywords: Medical image retrieval; medical multimedia data; visual information search; Web 2.0